2014
DOI: 10.5901/mjss.2014.v5n10p95
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Foreign Direct Investment on Economic Growth: Evidence from South Africa

Abstract: Foreign direct investment amongst other mechanisms provides capital inflow

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
2
10
0
2
Order By: Relevance
“…As can be observed, the OLS estimates indicate a surprisingly negative and significant coefficient on FDI and yet a produces a positive and significant coefficient on domestic investment. Note that these results concur with that obtained from the study of Mazenda (2014) for South Africa and Rahman (2015) for Bangladesh, albeit using different econometric techniques. Other results reported in Table 1 include a correct negative yet insignificant coefficient on inflation, a negative and insignificant coefficient on population and a negative and significant coefficient on terms of trade.…”
Section: Qar Regression Estimation Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As can be observed, the OLS estimates indicate a surprisingly negative and significant coefficient on FDI and yet a produces a positive and significant coefficient on domestic investment. Note that these results concur with that obtained from the study of Mazenda (2014) for South Africa and Rahman (2015) for Bangladesh, albeit using different econometric techniques. Other results reported in Table 1 include a correct negative yet insignificant coefficient on inflation, a negative and insignificant coefficient on population and a negative and significant coefficient on terms of trade.…”
Section: Qar Regression Estimation Resultssupporting
confidence: 89%
“…We also present a review of studies for South Africa and we consider this important as these studies are more closely related to our current study. To the best of our knowledge, the works of Fedderke and Romm (2006), Sridharam et al 2009, Masipa (2014), Mazenda (2014), Agrawal (2015), Sakyi and Egyir (2017) and Sunde (2017) suffice as an exhaustive list of previous empirical studies conducted on the South African economy using econometric techniques.…”
Section: Previous South African Studiesmentioning
confidence: 99%
“…He found that FDI inflows contributed negatively to total productivity and thus economic growth. This was mirrored by Mazenda's (2014) study on South Africa for the period 1960-2002.…”
Section: On the Negative Relationship Between Foreign Directmentioning
confidence: 82%
“…In addition, their study also observed a crowd-out of domestic investment from FDI -although this impact is restricted in the short-run (Mazenda, 2014). In a similar study, Sridharan, Vijayakumar and Chandra (2009) also studied the causal relationship between FDI and growth in the BRICS countries, using quarterly data from 1999 to 2007 for China, from 1992 to 2007 for India, and from 1990 to 2007 for South Africa (Mazenda, 2014). The results showed bi-directional relationships between FDI and growth for South Africa, while only a unidirectional relationship was observed for China and India.…”
Section: Foreign Direct Investment (Fdi) and International Trade In Amentioning
confidence: 92%
“…Confirming the positive spill-over from FDI and trade on output using aggregated time-series data in South Africa, Fedderke and Romm (2004) also confirmed the positive influence of FDI on growth from 1960 to 2002. In addition, their study also observed a crowd-out of domestic investment from FDI -although this impact is restricted in the short-run (Mazenda, 2014). In a similar study, Sridharan, Vijayakumar and Chandra (2009) also studied the causal relationship between FDI and growth in the BRICS countries, using quarterly data from 1999 to 2007 for China, from 1992 to 2007 for India, and from 1990 to 2007 for South Africa (Mazenda, 2014).…”
Section: Foreign Direct Investment (Fdi) and International Trade In Amentioning
confidence: 93%